Iraq : U.S. Regime Change Efforts and Post-War Governance. (U.S. Congressional Research., 2003)
Reviews U.S. efforts to remove Iraqi President Saddam Hussein and his Ba'ath Party regime from power in Iraq. Discusses past attempts to oust Saddam Hussein from power; emergence of an Iraqi opposition coalition and its fragmentation; efforts to rebuild an opposition strategy, including the role of the Iraq Liberation Act; continued debate over policy; Bush Administration policies toward Iraq; and post-war governance issues.